2015
DOI: 10.1002/pssc.201400366
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy study of phase transitions to ionic and superionic conductivity states in Ag2S and Ag2Se

Abstract: The percolation threshold (PT) temperatures Tc1,c2 of two non‐equivalent Ag+1,2 ions in Ag2S and Ag2Se lattices were determined from the temperature dependence of low‐frequency (25‐106Hz) impedance spectroscopy measurements. At PT temperatures Tc1≈200 K and Tc2≈ 334 K, an abrupt increase of the dielectric function ε1(ω) of Ag2Se crystal from a very large negative value, ε1 ≈‐109, to a very large positive value ε1≈ 106 was observed, which is assumed to result from the dipole relaxation. The strong peaks of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…Interesting results of superionics study are observed using dielectric spectroscopy (DS) method, that is often called impedance spectroscopy in literature [6]. This method is used for studying the temperature dependencies of functional features of frequency dependencies of dielectric loss tangent and dielectric relaxators distributions by relaxation time (Gavrilyak−Negami function).…”
Section: Introductionmentioning
confidence: 99%
“…Interesting results of superionics study are observed using dielectric spectroscopy (DS) method, that is often called impedance spectroscopy in literature [6]. This method is used for studying the temperature dependencies of functional features of frequency dependencies of dielectric loss tangent and dielectric relaxators distributions by relaxation time (Gavrilyak−Negami function).…”
Section: Introductionmentioning
confidence: 99%
“…Phase transitions and their influence on the electrical conductivity in Ag 2 S have been extensively studied experimentally in Ref. .…”
Section: Introductionmentioning
confidence: 99%
“…Интересные результаты исследований супериоников получены с помощью метода диэлектрической спектроскопии (ДС), который в литературе часто называют импедансной спектроскопией [6]. Этим методом исследуются температурные зависимости особенностей функций частотных зависимостей тангенса угла диэлектрических потерь и распределения диэлектрических релаксаторов по временам релаксации (функции Гавриляка−Негами).…”
Section: Introductionunclassified